Dampak Business Cycle pada Efisiensi Industri Properti yang Go Public di Pasar Modal Indonesia - David Sukardi Kodrat (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2006)
This research aim is to analyze the effect of efficiency business cycle in up and down stream condition by using real estate industries listed on Jakarta Stock Exchange. The analytical is used multivariate analysis of variance (Manova). The result shown that Wilks Lambda 0.364 and p-value 0.000.In up stream condition shows that variable efficiency: return on asset, return on equity, current ratio, debt to equity ratio and total liabilities to total asset have higher value than in down stream condition.In down stream condition, some assets are not used so that returns on asset to be low. Interest rate of commercial banks are high so interest expense to be big and finally real estate industries to be loss so return on equity to be low.Current ratio is lower because long term debt has been restructurization and rescheduling due to be current liabilities. There for asset financing for realestate industries are used debt than equity so total liabilities to total asset and debt to equity to be higher.Keywords: Business Cycle, efficiency, return on asset, return on equity, current ratio, debt to equity and total liabilities to total asset.